A reliability generalization meta-analysis of the Kaufman Domains of creativity scale - YÖRÜK, SÜREYYA (My University, 2023)
The Kaufman Domains of Creativity Scale (K-DOCS) is a self-reported rating scale that measures creative behaviors in five areas. Despite the vast amount of research on the scale, the internal consistency reliability of K-DOCS scores have not been examined. Specifically, there is no study on the overall reliability coefficients, the variation in the reliability of scores, and reliability induction. In the present study, reliability generalization meta-analyses were conducted to address these issues. The sample consisted of 56 studies that produced 60 Cronbach\"s alpha coefficients in total. The pooled alpha values were estimated to be.904 (total scale),.825 (Self/Everyday subscale),.858 (Scholarly subscale),.887 (Performance subscale),.867 (Scientific subscale), and.861 (Artistic subscale). The moderator analyses showed that the reliability estimates of K-DOCS total scores and Self/Everyday subscale scores did not differ with respect to any of the moderator variables. On the other hand, certain variables affected the alpha coefficients for Scholarly (educational level, SD of the age, and mean age), Performance (continent, educational level, ethnicity, Caucasian percentage, SD of the age, and mean age), Scientific (language, test version, continent, country, ethnicity, SD of the age, and mean age), and Artistic (continent, language, country, mean age, and total mean score) subscale scores. Finally, the reliability induction rate was 39.62%, and there were no statistically significant differences between the inducing and reporting studies with respect to the continuous variables (mean of the total score, means and SDs of the sample age, and percentages of female and Caucasian). Our findings indicate that the K-DOCS provides highly reliable scores. However, certain variables contribute to systematic errors in Scholarly, Performance, Scientific, and Artistic subscale scores. Hence, scores on these subscales should be interpreted with caution. Due to a high amount of variation in the reliability coefficients, reliability induction is not advised for the K-DOCS.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Gelişim Psikolojisi; Sosyoloji; Eğitim; Sanat; Social Sciences and Humanities; Psychology; Developmental Psychology; Sociology; Education; Art; Temel Bilimler (SCI); Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; Sosyal Bilimler Genel; PSİKOLOJİ, GELİŞTİRME; SANAT; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Natural Sciences (SCI); Arts & Humanities (AHCI); Social Sciences (SOC); PSYCHOLOGY; ARTS & HUMANITIES; SOCIAL SCIENCES, GENERAL; PSYCHOLOGY, DEVELOPMENTAL; ART; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Gelişim ve Eğitim Psikolojisi; Görsel Sanatlar ve Gösteri Sanatları; Social Sciences & Humanities; Developmental and Educational Psychology; Visual Arts and Performing Arts; K-DOCS; kaufman domains of creativity scale; reliability generalization meta-analysis; reliability induction